2001
DOI: 10.1152/ajpregu.2001.281.5.r1624
|View full text |Cite
|
Sign up to set email alerts
|

Does nitric oxide contribute to the basal vasodilation of pregnancy in conscious rabbits?

Abstract: Pregnancy produces marked systemic vasodilation, but the mechanism is unknown. Experiments were performed in conscious rabbits to test the hypotheses that increased nitric oxide (NO) production contributes to the increased vascular conductance, but that the contribution varies among vascular beds. Rabbits were instrumented with aortic and vena caval catheters and ultrasonic flow probes implanted around the ascending aorta, superior mesenteric artery, terminal aorta, and/or a femoral artery. Hemodynamic respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Previous work suggests that both systemic and central NOS were blocked. In a previous dose-response study, we found that the present dose was greater than that required to produce maximal pressor and bradycardia responses, indicating that NOS was maximally inactivated systemically (6). Moreover, this inhibitor is known to cross the blood-brain barrier (56), and Liu et al (32) demonstrated that the effects of a lower dose of intravenous L-NNA on baroreflex control of heart rate in conscious rabbits is mediated by a central action.…”
Section: Receptors With and Without Nos Blockade In Nonpregnant Andmentioning
confidence: 52%
See 1 more Smart Citation
“…Previous work suggests that both systemic and central NOS were blocked. In a previous dose-response study, we found that the present dose was greater than that required to produce maximal pressor and bradycardia responses, indicating that NOS was maximally inactivated systemically (6). Moreover, this inhibitor is known to cross the blood-brain barrier (56), and Liu et al (32) demonstrated that the effects of a lower dose of intravenous L-NNA on baroreflex control of heart rate in conscious rabbits is mediated by a central action.…”
Section: Receptors With and Without Nos Blockade In Nonpregnant Andmentioning
confidence: 52%
“…To test the hypothesis that pregnancy impairs baroreflex gain via actions of increased NO, we determined whether NOS blockade normalizes baroreflex gain in pregnant rabbits. In six rabbits, baroreflex curves were generated before and 105-134 min (depending on the occluder inflation chosen) after a bolus intravenous injection of the nonspecific NOS inhibitor N -nitro-L-arginine (L-NNA; 20 mg/kg dissolved in 10 ml of 0.5% sodium carbonate in water and then adjusted to pH 7.4) This dose produces maximal increases in mean arterial pressure and heart rate in rabbits (6). Following this experiment, rabbits were mated and the effect of L-NNA on baroreflex function was studied again at the end of gestation (day 30; term ϭ 31 days).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, MAP and HR rebounded quite quickly after delivery, to become similar to prepregnant values by postpartum day 2. Previous research indicates that nitric oxide contributes to the systemic vasodilation, hypotension, and tachycardia, since nitric oxide levels are increased and blockade of nitric oxide synthase increases MAP, decreases systemic vascular conductance, and decreases HR, more in pregnant than in virgin animals (5,14,50). Nitric oxide may increase secondarily to elevations in estrogen and/or relaxin (25).…”
Section: Changes In Map and Hr During Pregnancy And The Immediate Posmentioning
confidence: 99%
“…Increased synthesis of nitric oxide (NO) by the vascular endothelium likely contributes to vasodilation and decreased vasoconstrictor responses in pregnant animals, including humans. However, peripheral NO mechanisms cannot fully account for changes in blood pressure regulation in pregnancy (Brooks et al, 2001; McLaughlin and Conrad, 1995; Sladek et al, 1997). In addition to changes in the peripheral vasculature, the central nervous system (CNS) homeostatic systems for control of both blood volume (Lindheimer and Davison, 1995) and the autonomic nervous system (Brooks et al, 1997; Greenwood et al, 2001; Masilamani and Heesch, 1997; O’Hagan and Casey, 1998) are reset and contribute to the hemodynamic profile characteristic of normal pregnancy.…”
Section: Introductionmentioning
confidence: 99%